Groupes résobules et nilpotents - AOUIOUECHE, Khadidja; AOUN, Nora; FETHIZA A MARA, v c Nour Elhouda (university of eloued جامعة الوادي, 2014)
في مذكرتنا عالجنا جزء مھم من نظریة الزمر وھي الزمر المنتھیة التحلیلیة والزمر المنتھیة معدومة القوة,كما ذكرنا التعاریف الرئیسیة للزمر ,الزمر الجزئیة وایضا الخصائصالاساسیة لسلاسل الزمر الجزئیة. نقدم في الجزء الاخیر دراسة مكثفة عن الزمر التحلیلیة و الزمر معدومة القوة وافكار بسیطة للمقارنة بینھما(الزمر التحلیلیة والزمر معدومة القوة)مع امثلة مھمة.n our memoire, wetreat a partion theoris groups is solvable and nilpotent finite groups that we rappellont the moin definitions of groups, subgroups and also fondamontales properties series of subgroups. We present in section dérinre intensive study of solvable groups and nilpotent groups with a simple idea comparaisant (between solvable groups and nilpotent groups) with examples matter.
mémoire licence matimatuque
Keywords: الزمرة/الزمر المشتقة/الزمرة الجزئیة/سلاسل الزمر/تشاكل/الزمر التحلیلیة/الزمر معدومة القوة.; Groups/derive groups/subgroups/series of subgroups/morphism/solvables groups/ nilpotents groups.